Innovation in Disaster Risk Financing for Developing Countries : Public and Private Contributions - World Bank (Washington, DC, 2015)
This report aims to advance the dialogue on creative, forward-looking solutions for developing countries by presenting recent innovations on disaster risk financing and insurance developed by the private markets as well as the international donor community, from the macro (government) level down to the micro (household) level. It discusses how these innovations can be adapted and implemented in developing countries to better protect efficiently those countries against the financial consequences of natural disasters. Section one provides an introduction to the economic and fiscal impacts of natural disasters on developing countries. Section two examines examples of innovation in the private insurance and capital markets that may have applications in sovereign disaster risk financing for developing countries. Section three examines how innovations coming out of mature property catastrophe risk insurance (PCRI) markets could serve in low and middle-income countries. Section four considers how innovation is taking seed in creative disaster micro insurance programs in low- and middle-income countries. Section five wraps up the report with brief concluding remarks.